2014
DOI: 10.5867/medwave.2014.09.6023
|View full text |Cite
|
Sign up to set email alerts
|

Nonattendance to medical specialists’ appointments and its relation to regional environmental and socioeconomic indicators in the Chilean public health system

Abstract: In Chile, socioeconomic factors and the management of healthcare resources have greater influence on the nonattendance of patients to medical specialists’ appointments than environmental factors; therefore, this phenomenon may be avoidable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Some examples of absenteeism studies in Latin America also estimated variable rates: 11% in Costa Rica, 26 17% in Mexico, three studies from Argentina with nonattendance of 14% in Rosario, 27 22.7% in HIBA, 28 30% in the Mandirola study, 29 25.57% in Sao Paulo Brazil, 30 and between 8% and 20% in Chile's public system stratified by specialty and region. 31 These nonattendance rates present similar variability and heterogeneity between specialities, settings, and populations studied in concordance with other geographic areas estimations. Our estimations presented in this study are consistently within this range of variability.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Some examples of absenteeism studies in Latin America also estimated variable rates: 11% in Costa Rica, 26 17% in Mexico, three studies from Argentina with nonattendance of 14% in Rosario, 27 22.7% in HIBA, 28 30% in the Mandirola study, 29 25.57% in Sao Paulo Brazil, 30 and between 8% and 20% in Chile's public system stratified by specialty and region. 31 These nonattendance rates present similar variability and heterogeneity between specialities, settings, and populations studied in concordance with other geographic areas estimations. Our estimations presented in this study are consistently within this range of variability.…”
Section: Discussionsupporting
confidence: 86%
“…Our nonattendance rates are similar to those reported in other systems with a public payer predominance, such as the Chile study. 31 Because of the consistent variability of nonattendance in different settings, it is strongly recommended that local estimates are used in the design of effective interventions to improve adherence with outpatient healthcare scheduled appointments.…”
Section: Discussionmentioning
confidence: 99%
“…Applying Poisson regression models with random components, they analyzed the relationship between no-shows and environmental and socioeconomic regional indicators. They found that socioeconomic factors and healthcare resources management could influence no-shows more than environmental factors [35]. Samorani et al (2022) studied racial disparity in the context of predicting no-shows using a machine learning algorithm.…”
Section: Predicting No-showsmentioning
confidence: 99%
“…b) Predicting patients’ behaviour. To this end, researchers have used diverse statistical methods, including logistic regression [ 5 , 20 , 22 , 40 ], generalised additive models [ 43 ], multivariate [ 5 ], hybrid methods with Bayesian updating [ 1 ], Poisson regression [ 41 ], decision trees [ 12 , 13 ], ensembles [ 14 , 37 ], and stacking methods [ 46 ]. Their efficiency depends on the ability of predictors to compute the probability of no-show for a given patient and appointment.…”
Section: Introductionmentioning
confidence: 99%